Pressure Sensibility of Conductive Rubber Based on NBR- and Polypyrrole-Designed Materials - França, Débora; Rebessi, Ana Cláudia; Camilo, Fernanda Ferraz; Souza, Fernando G.; Faez, Roselena (Frontiers in Materials, 2019)
Conductive rubbers combine features such as elasticity and electrical conductivities. Here, we developed an elastic conductive material based on nitrile rubber (NBR) and polypyrrole (PPy) by melt processing. PPy was also synthesized in three different media as silver (PPy-Ag), organomontmorillonite (PPy-OMt) and silver-organomontmorillonite (PPy-Ag-OMt) before mixture with NBR. Chemical structure, morphology, and stress-strain properties were evaluated. Pressure sensibility was evaluated in the range of 0-67 MPa during ten cycles. During the compression and expansion processes, the electrical conductivity changes from high to low values and the difference of loading and unloading cycles demonstrate the repeatability and low hysteresis. The organomontmorillonite clay improves the homogeneity of particles into the matrix and based on SEM images the dispersity follows the sequence PPy-OMt, PPy-Ag-OMt and PPy-Ag-OMt. This behavior affects the electrical conductivity, mechanical and electromechanical properties. The higher elastic modulus for composites compares to neat NBR is assigned to the reinforcing effect of the fillers. NBR/PPy-Ag-OMt (5wt.%) is the best material in the absolute value of Scomp (46.3 %/MPa) and the Scomp/hysteresis ratio (8.5%). In spite of different formulations displayed the best performance on the evaluated criteria (highest absolute conductivity, the highest percentage change in conductivity, lowest hysteresis and lack of sample disruption), we can suggest that a lower amount of conducting particles benefits the reticulation process (as observed by the gel fractions values). Additionally, the possibility to use mechanical processing to obtain large scales pressure sensor materials are without doubts the most important outcomes for this research area.